A RESEARCH STUDY ON THE PSYCHOLOGICAL WELL-BEING AND PERFORMANCE OF EMPLOYEES IN MSMES IN THOOTHUKUDI DISTRICT - K, Zeenath Muscoora.; Nallathambi, J. Immanuel (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Psychological wellness is strongly linked to personal and professional outcomes, and its subjective nature means individuals' self-perceptions play a crucial role. When employees enjoy good mental health, they're more likely to thrive. The demand to boost employees' psychological wellness is growing, as it's vital for optimal job performance. Research reveals significant differences in psychological wellness among MSME employees, except when it comes to gender. Factors like environmental mastery, self-acceptance, life purpose, and positive relationships with others have a substantial, positive impact on job performance in MSMEs. To enhance psychological wellness among MSME employees, they should cultivate contentment with their accomplishments, be open to self-improvement, and efficiently fulfill their duties. Additionally, nurturing strong friendships and clarity on life's direction and purpose are essential.